2023
DOI: 10.1002/imhj.22072
|View full text |Cite
|
Sign up to set email alerts
|

Using the candidacy framework to conceptualize systems and gaps when developing infant mental health (IMH) services: A qualitative study

Fifi T. H. Phang,
Alicia Weaver,
David N. Blane
et al.

Abstract: The development of infant mental health (IMH) services globally is still in its early stages. This qualitative study aims to understand the challenges of setting up IMH services and explores the views and experiences of 14 multi‐disciplinary stakeholders who are part of the IMH implementation group in a large Scottish health board. Six major themes were identified through thematic analysis. This paper examines the most prominent theme “Systems” alongside the theme “Gaps in Current Service”. The theoretical fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Our recent research into the development of IMH services found that professionals shared a concern that the service might not be accessed by infants most in need (Phang et al., 2023).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent research into the development of IMH services found that professionals shared a concern that the service might not be accessed by infants most in need (Phang et al., 2023).…”
mentioning
confidence: 99%
“…It may be, for instance, that these adults do not realise that their infants are candidates for a service and/or have a right to access it (if, indeed, they are even aware of its existence). (Phang et al., 2023)…”
mentioning
confidence: 99%